Glycan Profiling Shows Unvaried N-Glycomes in MSC Clones with Distinct Differentiation Potentials - Wilson, Katherine M.; Thomas-Oates, Jane E.; Genever, Paul G.; Ungar, Daniel (Frontiers in Cell and Developmental Biology, 2016)
Different cell types have different N-glycomes in mammals. This means that cellular differentiation is accompanied by changes in the N-glycan profile. Yet when the N-glycomes of cell types with differing fates diverge is unclear. We have investigated the N-glycan profiles of two different clonal populations of mesenchymal stromal cells (MSCs). One clone (Y101), when differentiated into osteoblasts, showed a marked shift in the glycan profile towards a higher abundance of complex N-glycans and more core fucosylation. Yet chemical inhibition of complex glycan formation during osteogenic differentiation did not prevent the formation of functional osteoblasts. However, the N-glycan profile of another MSC clone (Y202), which cannot differentiate into osteoblasts, was not significantly different from that of the clone that can. Interestingly, incubation of Y202 cells in osteogenic medium caused a similar reduction of oligomannose glycan content in this non-differentiating cell line. Our analysis implies that the N glycome changes seen upon differentiation do not have direct functional links to the differentiation process. Thus N-glycans may instead be important for self-renewal rather than for cell fate determination.